EFFECT OF LOW-COST EMG FOR LEARNING MUSCLE CONTRACTIONS IN SPORT COLLEGE STUDENTS - Pramono, Bayu Agung; Siantoro, Gigih; Marsudi, Imam; Muhammad, Heryanto Nur; Noordia, Anna; Mustar, Muhamad Yusvin (Universitas Negeri Surabaya, 2023)
Surface electromyography (SEMG) is an application that helps coaches and athletes recognize and understand muscle contractions during practice and matches. Unfortunately, this tool is very expensive, so it is necessary to develop SEMG, which is cheap but has the potential to detect muscle contractions during movement. This research aims to develop an inexpensive SEMG for detecting muscle contractions. 10 sports students participated in this study, and they were active in carrying out measured and programmed physical activities four times a week. This research is an experimental study; all students will do barbell squats at 80% of the maximum load. Differences in muscle contractions on the SEMG sensor during concentric and eccentric contractions will be analyzed using the paired sample t-test. The results of this study found a difference in the amplitude of the two muscle contractions with p <0.05; besides that, for the first test, this tool was successful in describing a picture of the amplitude that continues to decrease in muscle contractions in fatigued conditions, although there needs to be an additional indicator in assessing the condition tired for SEMG. This study concludes that the SEMG sensor can detect muscle contractions due to a sports movement. Initial experiments in this study successfully detected muscle contraction signals due to different movements used low cost SEMG; then, it needs to be developed better to reduce noise due to electronic devices' influence around SEMG.